Algorithm for the Choice of Anticoagulant for Patients with Atrial Fibrillation - Yu. P. Skirdenko; N. A. Nikolaev (Столичная издательская компания, 2020)
Aim. To evaluate the effectiveness of the anticoagulant choice algorithm in the prevention of complications of atrial fibrillation (AF). Material and methods. Patients with AF (n=98) were included into observational prospective study. The level of adherence to treatment, risk of food interactions and presence of CYP2C9 and VKORC1 genes mutations were determined at the initial examination. These indicators were necessary to specify an eligible anticoagulant according to the evaluated algorithm. Therapy was prescribed by the attending physician. Hemorrhagic and thromboembolic complications were assessed at the next examination after 24 weeks. Results. Hemorrhagic complications were observed in 31.6% of patients during the follow-up. Their number was comparable in individuals taking antiplatelet agents and direct oral anticoagulants (DOACs) (χ2=1.44; p<0.49, Pearson) and significantly more in individuals taking warfarin (as compared to DOACs: χ2=25.08; p<0.000, Pearson; and antiplatelet agents: χ2=34.32; p<0.000, Pearson). Thromboembolic complications were reported in 8.16% of patients. Their number was more in patients taking DOACs than warfarin (χ2=7.03; p<0.03, Pearson). Patients who had to take DOACs according to the algorithm, but in the study took warfarin, demonstrated significantly greater number of thromboembolic complications, with a comparable number of hemorrhagic complications. Patients who could take warfarin according to the algorithm, but in the study took DOACs, had significantly greater number of thromboembolic complications, with a comparable number of hemorrhagic complications. Conclusion. The results of the study demonstrated the potential for reduction in complications, especially thromboembolic, in the choice of anticoagulant using the algorithm; and reduction in complications of therapy, primarily with warfarin, due to the initial prescription of DOACs. The proposed approach, which consists in using the quantitative assessment of adherence to treatment, and only if necessary supplemented by the assessment of food preferences and/or pharmacogenetic studies, contributes to the treatment optimization.